Problems Faced by Undergraduate Students of Assam Agricultural University in Obtaining Scholarships, India - SANTOSH; MAYURI BORA (Archives of Current Research International, 2025)
In India, a number of academic scholarship programmes have been initiated in an effort to motivate students for improving their academic performance. The degree to which students are aware of the scholarship programmes, however, plays a significant role in their ability to obtain such scholarships. Even though India has a sizable number of scholarship programmes, it is unknown how well-informed students are about them. This study was conducted to find out the problems that students of Agricultural University encounter in obtaining the Scholarship Schemes and also to assess the awareness of the students on different types of Scholarship Schemes A stratified random sampling method was used to include Two hundred forty undergraduate students from Assam Agricultural University as respondents in the study. A questionnaire was prepared and collected data online through "Google Form". Frequency, percentage, mean, standard deviation, and correlation test were done for analyzing the data. The data on problems faced by students in availing scholarship revealed that that majority of the respondents (52.92%) were facing moderate problem. The calculation of the correlation coefficient between respondents’ awareness of various scholarship programs and their problems revealed that it was significant at the 0.01 level(2-tailed).